The Role of e-Berpadu in Addressing the Lex Imperfecta of Article 143 Paragraph (4) of the Indonesian Criminal Procedure Code - Djaman, Riska Pratiwi; Mokoagow, Jemmy; Lasabuda, Hajim; Noerdin, Eldy (Dinasti Research, 2025)
This study examines the role of the e-Berpadu system in addressing the lex imperfecta nature of Article 143 paragraph (4) of the Indonesian Criminal Procedure Code (KUHAP), which obliges prosecutors to provide case files to suspects or their legal counsel but prescribes no sanction for non-compliance. The research was conducted at the Kotamobagu District Court using a qualitative approach that combined interviews, observations, document analysis, and focus group discussions. The findings reveal that e-Berpadu enables digital access to case files for legal counsel and supports the fulfillment of the right to information. No significant technical barriers were identified in its implementation. However, the case file access feature is neither a core component of the system’s design nor emphasized in its official dissemination, leaving many defense lawyers unaware of its availability. The study concludes that although e-Berpadu can function as a supplementary tool to ensure access to case files, it cannot substitute the prosecutor’s mandatory obligation under KUHAP